The current situation of digital transformation in Chinese higher education institutions: A SWOT–PEST analysis using the modified priority needs index - Chen, Huanli; Tuntinakhongul, Ampapan (Edelweiss Applied Science and Technology, 2026)
This study investigates the current situation of digital transformation in Chinese higher education institutions (HEIs) by examining internal and external environments through a SWOT–PEST framework. A dual-response questionnaire was administered to 384 respondents (336 students and 48 lecturers) from HEIs in Beijing, China. The internal environment was operationalized through four elements of educational administration (data management, human resources management, financial management, and academic affairs management), while the external environment was assessed using the PEST dimensions (politics, economy, society, and technology). Mean scores for current and desired conditions were analyzed using the modified Priority Needs Index (PNI modified) to classify internal strengths/weaknesses and external opportunities/threats. Results indicate that data management constitutes the main internal weakness, whereas human resources management, financial management, and academic affairs management are relative internal strengths. Externally, the economic dimension emerges as the primary threat, while political, social, and technological aspects are perceived as key opportunities. These findings provide an empirical basis for designing more targeted and feasible digital transformation strategies for Chinese HEIs.